Releasing prisoners, redeeming communities: reentry, race and politics - Thompson, Anthony C. (New York University Press, 2008)
Reentry, race and stigma -- Media influence on public perceptions of prison life -- Women : the afterthought in reentry planning -- Reentry and housing -- Reentry and health care -- Reentry and unemployment -- Reentry and the political process -- Reentry and parole -- Reentry courts -- Conclusion